Civil Administration on the Suburbs of Al–Kufa (Journal of the College of Education for Women, 2019)
We have found through research , that administrative institutions on the outskirts of Kufa and their management is not as important as administrative institution in place that were associated with it and subject to its control ,as it often was express power , or poor ( if true ) expression , directors of the center for the suburbs , as it became clear to our diversity of those administrative institutions and prominent role in the interest of the affairs of the people and society in all aspects of life , and are the functions and different staff from the highest authority the suburbs represented by house of representatives ( the workers ) ,then workers abscess and Al-dhaqan and not to mention for other jobs came the actions of Bhaltsier and monitoring economic and social aspects in people s lives ,such as publicans and workers charity and Mahtsiaun , also found through research that social status ,cultural , scientific and managerial expertise have been instrumental in the appointment of staff to assume managerial positions and work assignments on the outskirts of kufa , usually what are the persons and individuals with prestige and efficiency , competence , which helped to stabilize and population growth is evident in the outskirts of Kufa , and because the system of government in Kufa and its suburbs was centrally however the governors of Kufa who met their hand s the powers set representatives and staff profiles administrative components of the outskirts of Kufa ,has undergone these control that power and accountability , which contributed to the provisions of the control center to the suburbs and administrative subordination of the center .